(3GdeWGdH GdYGdjI HRhGFO GdeSGfjO GdKeGfjIs - (3CMeO Hf Ydj Hf eMeO GdcfGfj GdYSbdGfj, CHh GdaVd, TgGH GdOjf, GHf nMnLQ,J (B852 (3g` s
(3ChdgG (B:s
(3GdMeO ddg LGeY GdTJGJ Yf GdCMjGA hGdCehGJ HGNJdGa GddZGJ CeG HYO aEf GdETJZGd HGdYGde NUhUkG GdMOjK GdfHhi ef CaVd GdbQHGJ hbO LeY CFeJfG efg GdaJGJ Ydi GdeSGfjO hGdCHhGH GdeQJHGJ s
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde (B: " (3QCS GdYbd HYO GdEjeGf HGddg JYGdi GdJhOO Edi GdfGS MSHfG Gddg hfYe Gdhcjd s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
Keywords: (3GdMOjK h GdeUWdMs